2019
DOI: 10.1111/pai.13099
|View full text |Cite
|
Sign up to set email alerts
|

Adverse health outcomes associated with fetal alcohol exposure: A systematic review focused on immune‐related outcomes

Abstract: Prenatal alcohol exposure (PAE) has well‐known teratogenic effects on the developing fetus, potentially resulting in neurologic impairments. However, there is increasing interest regarding other potential adverse health outcomes related to prenatal alcohol exposure. The objective of this study was to undertake a systematic review to identify all the available clinical and preclinical literature investigating immune‐related outcomes in offspring with PAE. A systematic review searching four electronic databases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 48 publications
(163 reference statements)
0
22
0
Order By: Relevance
“…Strategic treatments eliminate tangible factors that contribute to weaken the immune system. Some examples of such factors, based on existing studies, include titanium dioxide, air pollution, chlorpyrifos, aluminum sulfate, prenatal alcohol exposure, ZnO, oil fly ash, and many others (3)(4)(5)(6)(7)(8)(9). Also the real life exposure scenario in which we are exposed continuously to combination of stressors influences in the long term the immune system and the response of the organism to the viral stressors (10)(11)(12)(13)(14).…”
Section: Towards Effective Covid-19 Vaccines: Updates Perspectives Amentioning
confidence: 99%
“…Strategic treatments eliminate tangible factors that contribute to weaken the immune system. Some examples of such factors, based on existing studies, include titanium dioxide, air pollution, chlorpyrifos, aluminum sulfate, prenatal alcohol exposure, ZnO, oil fly ash, and many others (3)(4)(5)(6)(7)(8)(9). Also the real life exposure scenario in which we are exposed continuously to combination of stressors influences in the long term the immune system and the response of the organism to the viral stressors (10)(11)(12)(13)(14).…”
Section: Towards Effective Covid-19 Vaccines: Updates Perspectives Amentioning
confidence: 99%
“…8 More recently, the life course consequences of exposure to perinatal environmental toxins due to maternal smoking, pollution, alcohol, and consumption of drugs of abuse have increased the scope of intensive programming investigations. 9,10 Epidemiological studies typically employ public medical databases and focus on diagnostic end points. This approach provides powerful distribution patterns, but lacks the ability to determine causative mechanisms by which malnutrition and other early challenges alter the physiology of maturation, life course disease pathology, and aging.…”
Section: Dohad and Heart Diseasementioning
confidence: 99%
“…The first study in this area, a small case study of children with fetal alcohol syndrome (FAS; at the most severe end of the FASD spectrum), showed that children with FAS had increased rates of major and minor infections compared to controls [21], and this increased infection risk associated with prenatal alcohol exposure has been replicated in other studies as well [22][23][24]. In addition, impairments in cell-mediated and humoral immunity [21] and increased risk of dermatitis [25], eczema [26], and certain cancers [27] have also been reported (reviewed in [28,29]). All of these immune-related changes may be a result of alcoholinduced programming of the immune system, altering the production and/or release of immune mediators.…”
Section: Introductionmentioning
confidence: 95%